Interactions in nanosilica-polyurethane composites evidenced by plate-plate rheology and DMTA - Martín Martínez, Jose Miguel (2005)
Fumed nanosilicas with different degree of silanization were used to obtain nanosilica-polyurethane (TPU) composites to modify their rheological and mechanical properties. The higher the silanol content of the nanosilica, the higher the storage modulus and the thermal stability of the silica-TPU composite. DMTA experiments confirmed that the TPU-silica interactions increased by increasing the silanol content of the nanosilica.